Impacto do uso abusivo de álcool : estudo em famílias de trabalhadores da construção civil - Martins, Beatriz Ferreira (2013)
The increasing use of drugs and its effects on families and society have become a serious problem for public health, especially to family's and worker's health. The study´s objective was to analyze the impact of alcohol abuse on families of construction workers. An exploratory - descriptive and mixed approach study was performed in Maringá-Paraná, with relatives of 11 construction workers with a diagnosis of acute or chronic alcohol intoxication and registered in the Poison Control Center at the Regional University Hospital of Maringa in the period of January to June 2013. The data source was the record of Toxicology Intoxication Occurrence and / or Other Drug Abuse (OT/IA), and the instruments were two scripts for the semi-structured interview - Worker Screenplay and Family Screenplay-; two rating scales, Family Risk Scale and the Rating Scale of Family Overload, and a field journal. Data collection was performed by household interviews and documentary analysis. The interviews were recorded and analyzed using descriptive analysis and thematic content analysis. The scale results analysis was performed by sizing the scores percentage of responses to the items. The research project was submitted to the Ethics Committee on Research Involving Human Subjects at the State University of Maringa, opinion number 207.377/2013. All workers were male, average age 44 years old, low education and low individual income, and the most frequently cited occupation was bricklayer. The family resident average in the same household was five and the rooms average was six and four other families had another alcoholic family member beyond the worker. Ten respondents were female relatives, eight being the worker´s wives, with average age of 42 years old; also with low education and low individual income. The impact of alcohol abuse in families was grouped and discussed from three thematic units: Family relationships and alcohol abuse, Alcohol destroying the marital bond; Family violence and reflections on the living environment. The stratification of families´ social risk scored ten families in social risk and characteristics such as unemployment, low sanitation, hypertension and drug addiction in a family member. Five families were under maximum social risk as they didn´t have bedbound or severely malnourished member. The analysis of the objective burden of families pointed transporting worker (100%) , the preparation or assist in preparing food (81,8%), taking care of family money (72,7%) or reminding the worker of personal hygiene (63,6%). The subjective burden of family members indicated a high difficulty in performing daily tasks to assist workers followed by monitoring or recollection of medical appointments (85,7%). Although the study was conducted with a specific population, it intends to bring support to the families with workers in alcohol use, often in a state of despair to health and social care services, and that effective and specific measures should be applied by health professionals, especially the nursing staff at all levels of care.